Congestive Loss in Wireless Ad hoc Network: Network Performance Analysis - Nahar, H.; Muslim, Z.; Shibghatullah, A. S.; Sahib, S. (WCSIT, 2011)
Communication in wireless network is quite susceptible to mobility, nodes capacity and power consumption level. These might contributes to the major problem of TCP performance degradation where there are highly potential of packet loss and packet reordering. In this research, we manage to observe the impact of packet behavior once the node’s capacity is limited when passing on-going data. This condition occurs when the node’s buffer starts to be overloaded. A simulation study by using OPNET Modeler 14.5 is conducted to achieve the purpose. A static ad hoc topology with the size of users (2n where n=0, 1, 2, 3 and 4) is used to observe several parameters such as throughput, number of packet dropped, retransmission count and end-to-end TCP delay. The results show that the size of buffer for ad hoc node influence the network performance whenever number of users is changed. In future, we plan to extend this study in a way of deeply understanding the effect of mobility in wireless network.